Symbolic Communication of the Tuntung Pandang (Kondang) Skullcap as a Regional Symbol of Tanah Laut Regency - Ikram Noor Kautsar; Nurannafi Farni Syam Maella; Harliantara Harley Prayudha; Iwan Joko Prasetyo; Tony S Soekrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study collected data through analysis of the Tanah Laut Regency news portal which reviewed the Regent's use of the Tuntung Pandang skullcap at various official events. A qualitative approach was used to explore the symbolic meanings contained in this skullcap and how society received and communicated these meanings. The research results show that the Tuntung Pandang Kopiah is not just traditional clothing or a symbol of formality, but is also an important marker of cultural identity for the people of Tanah Laut. This symbol contains values ​​such as tradition, authority, and courage which are closely related to the position of Regent. This research provides a new contribution by describing the complex relationship between the symbol (Tuntung Pandang skullcap), the object (Regent of Tanah Laut), and the community's interpretation or understanding of the symbol. Through the approach of Peirce's semiotic theory and Ogden and Richards' Triangle Theory, this research highlights that cultural symbols not only have aesthetic value but are also an important tool in building the social and cultural identity of a community. This research also explores the meanings implicit in the use of symbols and how these symbols play a role in building identity and social solidarity in local communities.. Keywords: Tuntung Pandang skullcap, cultural symbol, Tanah Laut Regency, semiotic triangle theory, cultural identity